Produção de biopolímeros fúngicos a partir da fermentação submersa de Phoma dimorpha - Luft, Luciana (2021)
Research with fungi is growing due to the possible bioproducts from its cultivation, as well as its different applicability. Fungal biopolymers can be produced from the fermentation process of these microorganisms. Alternative strategies for obtaining these compounds, which have characteristics of biocompatibility and biodegradability, are extremely necessary. Studies show that species of genus Phoma are sources of bioactive biopolymers with several specific activities. The species Phoma dimorpha has stood out for having a relevant herbicidal potential, however, research regarding the production of biopolymers by this species has not been found. In view of this, the objective of this work was to investigate the potential for the production of intra and extracellular biopolymers by submerged fermentation from fungus Phoma dimorpha. The fermentation conditions (culture medium and process parameters) were defined in previous studies developed by the research group. The first experimental stage consisted of the concentration (membranes and adsorption) and recovery of extracellular biopolymers (acid precipitation). In the second stage, the extraction and characterization of intracellular biopolymers was performed. Different methods, such as ultrasound-assisted extraction (with direct and indirect sonication) and pressurized hot water extraction, were evaluated in comparison with a conventional extraction method (hot water). Structural characterization, solubility, emulsification index and holding capacity were carried out. And in the third stage, the production of extra and intracellular biopolymers was evaluated with the addition of different carbon sources in the fermentation (crude glycerol, rice bran and brewer's spent grain), as well as the effect on the properties of fermented broth (pH, density, surface tension, and herbicidal activity) and on the emulsification index of compounds. From the concentration experiments, there was an increase of approximately 40% in the concentration of biopolymers and a decrease of around 35% in the surface tension of fermented broth using microfiltration membrane. The ultrafiltration membrane showed lower concentration results, probably due to the fouling mechanism. The adsorption of biopolymers with different adsorbents was effective, mainly with activated carbon, where a recovery of 98.5% was achieved. From this study, it was possible to conclude that the increase at concentration of biopolymers in the fermented broth led to an increase in herbicidal activity and a decrease in surface tension. Therefore, the results are promising for future applications, as a concentrated solution of biopolymers can increase weed control. As for intracellular biopolymers, the highest concentration (12.02%) was obtained with the ultrasound-assisted extraction process with direct sonication. The results for ultrasound with indirect sonication were lower (0.32-1.70%) than for conventional extraction with hot water (3.12-6.58%). Extraction with pressurized hot water showed results with greater variation (1.71 to 8.64%). And finally, the most appropriate additional carbon source according to the emulsification index was crude glycerol, which led to a decrease in surface tension. However, concentrations of intracellular and extracellular biopolymers found were lower than previous studies. From the results, it was concluded that the species Phoma dimorpha, besides having herbicidal potential, could be considered a promising source of biopolymers with bioemulsifying properties.